A Sense of Time and Place: Gilbert Stelter's Contribution to Urban History - Taylor, John (Urban History Review / Revue d'histoire urbaine, 2000)
These remarks were presented at “The Urban Academic,” a conference in honour of the retirement of Dr. Gil Stelter, September 26, 1998, at the University of Guelph. The conference was presented by the History Department of the university.Gil Stelter was the first president of the Canadian Urban Group after it was founded in 1971 at the annual meeting of the Canadian Historical Association in St. John's, Newfoundland. In retirement, Gil combines his writing on urban history with the hybridizing of day lilies. He is currently president of the U.S.-based Urban History Association.